Emotional resonance and rational reflection in hybrid space: a cross-platform study of public opinion evolution in youth digital collective action - Jia Jia Hao; Xiaotong Dong; Yingyue Li; Shuang Li (Computational Urban Science)
Abstract Objective/Background Social media has become deeply integrated into urban life, and digital collective actions by young people rooted in physical spaces are becoming increasingly common, posing new challenges to urban governance. There is an urgent need to understand the dynamic evolution of cross-platform public opinion in such events to provide a basis for precise governance. Research process/Methodology Taking the “Night Riding to Kaifeng” incident as an example, this study integrated 27,216 data points from the Weibo (mass communication) and Zhihu (knowledge community) platforms. Using the life cycle theory to divide public opinion into stages, the study analyzed public emotions at each stage using the emotion dictionary and employed the LDA topic model to explore the evolution of themes. Research conclusion/Results The study found Weibo exhibited “emotional resonance” with dominant positive emotions, effectively mobilizing offline action, while Zhihu featured diverse emotional profiles with rational debate emphasis. Grounded in collective action theory and urban social movement theory within hybrid space, this research uncovered the organizational logic and cross-platform expression patterns of emergent youth collective action in social media contexts. Research value/Significance This study deepens understanding of public opinion complexity in collective emergency incidents within social media contexts, offering empirical and theoretical foundations for multi-tier early warning systems, agile collaborative governance, and youth-inclusive resilient urban development.